Polish Independent Press Summary, no. 36 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Informator - Region Środkowo-Wschodni, no. 158 (26 June 1988). Extract from Informator - Region Środkowo-Wschodni, no. 159 (9 July 1988). Extract from CDN - Głos Wolnego Robotnika, no. 242 (25 June 1988). Extract from Rzeczpospolita Samorządna, no. 10 (12 June 1988). Extract from Horyzont, no. 18 (19 June 1988). Table of Contents from Prawo i Bezprawie, no. 2/3(15/16) (February/March 1988). Extract from Prawo i Bezprawie, no. 2/3(15/16) (February/March 1988). Table of Contents from FA, no. 1 (1988). Table of Contents from Obecność, no. 21 (1988). Extract from Obecność, no. 21 (1988). Table of Contents from Bez Debitu, no. 4 (1987). Table of Contents from Krytyka, no. 27 (1988). Extract from Krytyka, no. 27 (1988).